Doing Quantitative Grounded Theory - Mark S. Rosenbaum (Grounded Theory Review: An International Journal)
All is data. Grounded theorists employ this sentence in their quest to create original theoretical frameworks. Yet researchers typically interpret the word “data” to mean qualitative data or, more specifically, interview data collected from respondents. This is not to say that qualitative data is deficient; however, grounded theorists may be missing vast opportunities to create pioneering theories from quantitative data. Indeed, Glaser and Strauss (1967) argued that researchers would use qualitative and/or quantitative data to fashion original frameworks and related hypotheses, and Glaser’s (2008) recently published book, titled Doing Quantitative Grounded Theory, is an attempt to help researchers understand how to use quantitative data for grounded theory (GT).